KEKERASAN SEKSUAL PADA ANAK DI INDONESIA (Tipologi, Respon Pemerintah Dan Hukum Islam) - Dahyul Daipon (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2016)
Indonesia is in a state of child abuse emergency, data each year has steadily increased as released by the Indonesian Child Protection Commission (KPAI) from 2011 to 2014 as follows, in 2011, 2178 cases of violence occurred, in 2012 there are 3512 cases, in 2013 there 4311 cases, in 2014 there are 5066 cases. Violence against children can occur within four (4) form, physical abuse, sexual, psychological and neglect. Of the four forms of child abuse, sexual abuse occupies the number of cases in each year. Both in the region and in the capital city of the country. Most cases occur in Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek). Sexual abuse not only happen in big cities but also in small towns even to the villages. In response, the Indonesian government through the leader of the country, President has issued a decree No. 1 of 2016 About the Child protection, it is the second amendment of Law No. 23 of 2002, the first amendement is Law No. 35 of 2014. The essence of the changes is the weighting punishment either principal and additional penalties. According to Islamic law, sexual abuse of children can be classified to ta'zir criminal offense, because there are no passages that describe the forms of punishment.